Radioatividade: uma proposta para o ensino de Química com utilização de simuladores - Prates, Bruno Ximenes (2021)
Simulators are computational software programmed to demonstrate situations analogous to scientific concepts, submicroscopic representations or even everyday facts through images and animations, facilitating their understanding. The difficulty in carrying out demonstrative experiments in the classroom, whether due to security, lack of structure, resources or even because the content deals with a complex subject for their realization, can be solved by the use of computer simulators, which requires a simpler structure. In this work, we seek to carry out a two-way approach, using historical contextualization together with the use of simulators for teaching Radioactivity content. At first, the textbooks approved for use in high school were evaluated to understand the different ways proposed to work on this content, the platforms that offer free simulators were listed and evaluated, as well as the simulators found in them and that are directly linked to the Radioactivity content. The aim of this work is to encourage the use of simulators as a tool to improve the teaching of chemistry and not only the proposed content. For this purpose, didactic material was elaborated, following the pillars of Active Technological Learning, aimed at the chemistry teacher, for use with his students, proposing historical context through texts, contextualized documentaries and explanatory videos that present the resources offered by the platforms as well as in their simulators that can be accessed through QR Codes available in the material.